Development of a solar-powered photovoltaic (PV) fault location system for medium voltage line in Tanzania - Ahmed, Salum; Mbuya, Benson H.; Kichonge, Baraka; Maagi, Mtaki Thomas; Kivevele, Thomas (Electrical engineering, 2025)
This paper presents a fault location system designed for medium-voltage (MV) distribution lines in Tanzania, where frequent outages disrupt economic and social activities. Existing manual fault location methods are slow and costly, while high-voltage solutions are expensive and unsuitable for MV systems. Inefficient fault detection extends restoration times, undermining grid reliability and impeding development in resource-constrained regions. This study aims to develop a solar-powered photovoltaic fault location system that leverages real-time current measurements analyzed from TANESCO’s operational data to reduce outage durations and enhance network resilience. Prototype integrates SCT013 current sensors and an ATmega328P-PU microcontroller, programmed via the Arduino IDE. The system continuously monitors fault currents and triggers GSM-based SMS alerts with precise GPS coordinates. Data analysis using MATLAB and Python evaluates system accuracy and response time. Tests on a 220 V radial feeder revealed detection times of 5–6 s a > 99% improvement over traditional manual methods (≈ 900 s). Mean Absolute Error (0.2325 A) and RMSE (0.234 A) confirm high precision relative to typical MV fault currents (50–500 A). These results demonstrate a robust, low-cost solution for autonomous fault localization, offering rapid, near real-time fault notification. This approach provides a practical solution for improving the reliability and resilience of Tanzania’s MV power distribution lines, contributing to the nation’s sustainable development goals.